Multiculturalism, Interculturalism, Transculturalism and The Reluctant Fundamentalist - Estévez-Saá, José Manuel (SARE: Southeast Asian Review of English, 2017)
The most influential theorists of multiculturalism and interculturalism have attempted a rigorous re-examination of their proposals, as demonstrated by recent publications such as “Interculturalism versus multiculturalism –The Cantle-Modood debate” (2015) and Multiculturalism and Interculturalism: Debating the Dividing Lines (2016). Both Ted Cantle and Tariq Modood have acknowledged the need to revise the concepts of interculturalism and multiculturalism as a response to the rapidly changing circumstances of contemporary societies. This paper seeks to: briefly review recent assessments of interculturalism and multiculturalism; attempt to establish a dialogue between the interculturalism-multiculturalism debate and the precept of transculturalism (Dagnino 2012, McLeod 2011); and exemplify the usefulness of the transcultural approach in the exegesis of literary fictions such as Mohsin Hamid’s The Reluctant Fundamentalist (2007), a novel that because it operates at the level of both multicultural and intercultural encounters is able to richly contribute to these debates and discourses. The paper argues for the salience of critical terms such as “transnational writer”, “transnational literature”, “transculturality” and “transculturalism” as they offer a critical vocabulary particularly appropriate for the study of the movements and migrations of people that are depicted with increasing regularity in twenty-first century literature in English.